2008
DOI: 10.6090/jarq.42.187
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Iron Tolerant Rice Lines Developed at IRRI under Field Conditions

Abstract: In the 2003 wet season, IR64 (check variety) and four lines of rice (Oryza sativa L.) developed at IRRI were cultivated in a field with iron (Fe) toxicity at Iloilo City, Philippines, and also under normal soil conditions at IRRI farm. Two of the lines used in the experiments were the near isogenic lines (NILs) of IR64, selected as Fe-tolerant lines in solution culture in the greenhouse. The other two lines were elite breeding lines that were selected as Fe-tolerant lines in the field trial at Iloilo. The tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 26 publications
1
24
0
2
Order By: Relevance
“…Secondly, there is a strong correlation between LBS and grain yield as seen in this study at 60 DAS and several others Audebert & Sahrawat, 2000;Elec et al, 2013;Onaga,Edema, & Asea, 2012). However, in some other studies no significant correlation between LBS and grain yield was observed (Nozoe et al, 2008;Sahrawat et al, 1996) as seen at 40 and 80 DAS. Level of correlation between the two traits is likely to depend on stress intensity, testing condition, and type of varieties used.…”
Section: Panicle Number Shoot Dry Weight (G/pot)supporting
confidence: 65%
See 1 more Smart Citation
“…Secondly, there is a strong correlation between LBS and grain yield as seen in this study at 60 DAS and several others Audebert & Sahrawat, 2000;Elec et al, 2013;Onaga,Edema, & Asea, 2012). However, in some other studies no significant correlation between LBS and grain yield was observed (Nozoe et al, 2008;Sahrawat et al, 1996) as seen at 40 and 80 DAS. Level of correlation between the two traits is likely to depend on stress intensity, testing condition, and type of varieties used.…”
Section: Panicle Number Shoot Dry Weight (G/pot)supporting
confidence: 65%
“…The reasons for the observed differences in performance of Bao Thai in the two field studies are not clear but it could be due to differences in soil type. While Elec et al (2013) observed good correlation between hydroponic screening and field testing others have not found similar results (Becker & Asch, 2005;Nozoe et al, 2008).…”
Section: Panicle Number Shoot Dry Weight (G/pot)mentioning
confidence: 96%
“…Thus, one of the factors that caused an increase in EC might have been an increase in the organic acids and Fe 2þ contents of the soil solution. The amount of Fe 2þ in soil solution tends to be high when the pH of the soil is low, because Fe 2þ in soil solution precipitates as various oxides and hydroxides at high pH (Nozoe et al 2008). The findings obtained in this study suggest that soil pH is one of factors responsible for EC.…”
mentioning
confidence: 60%
“…A high concentration of Fe 2þ in soil solution sometimes suppresses the growth of paddy rice (Nozoe et al 2008). In our previous papers, we suggested that the accumulation of Fe 2þ in soil solution was one of the factors related to the growth suppression of paddy weeds (Nozoe et al 2009;Nozoe et al 2010).…”
mentioning
confidence: 99%
“…Audebert and Fofana (2009) reported that for every increase in LBS by one grain, the yield is reduced by 500 kg ha -1 . There are a few other reports of a negative correlation between bronzing score and yield under Fe toxicity stress (Sahrawat et al, 1996;Nozoe et al, 2008;Onaga et al, 2013). The relation between LBS and grain yield could depend on the type and number of entries used, and experimental conditions.…”
Section: Selection Criteria Of Fe Toxicity Tolerant Varietiesmentioning
confidence: 99%